1997
DOI: 10.1044/0161-1461.2801.03
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Children With Language Impairment to Manipulate Topic in a Structured Task

Abstract: This study investigated the way in which 10 children with specific language impairment (SLI), 10 typical children of similar chronological ages (CA), and 10 typical children at similar levels of language functioning (LS) maintained topics that were introduced to them by an adult investigator. Two different types of topics were introduced in interaction with each child. One topic type involved verbal introduction of an object, the other involved verbal introduction of an event. Although most subject in all grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
9

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 20 publications
0
19
0
9
Order By: Relevance
“…Specific elicitation tasks are described repeatedly in the literature. For instance, Brinton et al (1997) developed a ‘topic task’ in which an examiner introduces a number of specific topics and encourages the child to develop that topic. The examiner takes a camera out of a bag and says to the subject ‘I got this for my birthday.…”
Section: Practical Considerations Of Sampling and Elicitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific elicitation tasks are described repeatedly in the literature. For instance, Brinton et al (1997) developed a ‘topic task’ in which an examiner introduces a number of specific topics and encourages the child to develop that topic. The examiner takes a camera out of a bag and says to the subject ‘I got this for my birthday.…”
Section: Practical Considerations Of Sampling and Elicitationmentioning
confidence: 99%
“…Brinton, Fujiki, and Powell (1997) concluded that formal testing of topic is not possible because the number of variables (contextual and personal) which impinge upon topic development and maintenance are impossible to control in a naturalistic setting. Estimates of ‘normality’ in topic management are impossible because of large variations in personal style (Brinton & Fujiki, 1985).…”
mentioning
confidence: 99%
“…A more global, interactive approach to language would be required from all those intervening in the pupil's educational process (the other teachers, family members), focusing on facilitating social communication across all contexts of action, along the lines proposed by Brinton, Fujiki and Powell (1997).…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with highly structured approaches that rely on procedures such as imitation, shaping, fading and generalization, and pursue objectives that mainly have to do with articulatory skills (Hodson & Paden, 1991) or morpho-syntactic skills (Fey & Cleave, 1997). A more global, interactive approach to language would focus on facilitating social communication by means of interactive modeling, appealing at times to conversations or narrations in order to achieve linguistic objectives (Brinton, Fujiki & Powell, 1997), and always pursuing a collaborative perspective in conjunction with the team of teachers and family.…”
Section: Models Of Support Characteristicsmentioning
confidence: 99%
“…As Brinton, Snow and Wesche (1989) pointed out, content-based approach provides a larger framework for language development, in which the focus is not only on fragmented examples of correct language forms, but also on interaction and discourse patterns. According to Brinton, Fujiki and Powell (1997), the relevance of the material to the learners" needs and purposes in this type of instruction provides them with an intuitively attractive condition for learning.…”
Section: Integrating Content and Language Instructionmentioning
confidence: 99%